Greening of the Mineral Economy--Take China for Example - Mingqiu WANG; Tatiana Samuseva Valentinovna (Communications of International Proceedings, 2024)
As people's standard of living improves, their demands on the ecological environment are becoming higher and higher. As mineral resources are an important pillar of the national economy, the traditional mode of exploitation often leads to resource depletion and environmental damage. Globally, the exploitation of mineral resources is facing increasingly high environmental standards. The green development of the mineral economy can help promote the transformation of the economic structure from the traditional resource-dependent to the green and low-carbon type, cultivate new points of economic growth, and improve the quality and efficiency of economic growth. Green development emphasizes the sustainable use of resources in the process of mineral resources development and ensures the harmonious coexistence of mineral resources development and the ecological environment. In short, the green development of the mineral economy is an important element in realizing sustainable economic and social development, and is of great significance in promoting the harmonious coexistence of human beings and nature and safeguarding the long-term development of the country.
Keywords: Mining economy; green development; ecology; sustainable development